PERAN KEPALA DESA DALAM PENGEMBANGAN DESA WISATA (Studi Kasus Desa Wisata Sangeh, Kecamatan Abiansemal, Kabupaten Badung) - Dewi, Desak Made Trisna Juliantari (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2024)
Tourism village development is the government's mission to improve community welfare through the development of productive businesses in the tourism sector in accordance with existing regional resources and potentials. The development of tourism villages requires the participation of village and community officials to support the progress of tourism villages. The participation of the village head is one of the important points in the development of tourism villages. This study aims to see and describe the role of the Village Head in the development of Sangeh Tourism Village. The method used will be a qualitative descriptive approach with data collection techniques through observation, interviews and documentation. The result obtained from this research is that the Head of Sangeh Village plays a role in becoming a bridge of cooperation between agencies and universities who want to provide coaching and training to the community. The village head and ranks also participated in the success of the Sangeh Festival which was used as a promotional event for Sangeh Tourism Village. The village head is also the initiator in making the mascot dance of Sangeh Village named